The comparison between fine motor skills traditional activities and multi-touch gestures screen design: expert reviews - Nor Azah Abdul Aziz (Tanjong Malim, 2019)
The comparison between fine motor skills traditional activities and multi-touch gestures screen design: expert reviews by Nor Azah Abdul Aziz